Comparative Analysis Using Pulsed-Field Gel Electrophoresis Highlights a Potential Transmission of Salmonella Between Asymptomatic Buffaloes and Pigs in a Single Farm - Santana, André Marcos; Silva, Daniela Gomes da; Maluta, Renato Pariz; Pizauro, Lucas José Luduverio; Simplício, Kalina Maria de Medeiros Gomes; Santana, Clarissa Helena; Rodrigues, Sarah de Andrade Dias; Rodrigues, Dália dos Prazeres; Fagliari, José Jurandir (Frontiers in Veterinary Science, 2020)
Buffaloes and pigs play an important epidemiological roll in the Salmonella infection cycle, and asymptomatic animals can act as key component in the dissemination of the disease by horizontal, vertical and cross-species transmission. Our study aimed and was able to confirm evidences of a cross-species transmission of Salmonella Agona between asymptomatic buffaloes and pigs. Also, we described Salmonella infection within the pig production phases, involving serotypes Agona, Senftenberg and Schwarzengrund. Rectal samples were collected from Jafarabadi buffaloes (n=25) and Piau pigs (n=32), located on a single farm. Salmonella Agona was isolated from lactating buffaloes, gilts, pregnant sows and weaned pigs, Salmonella Schwarzengrund from lactating sows and Salmonella Senftenberg from gilts, pregnant sows, lactating sows and weaned pigs. Pulsed-field Gel Electrophoresis protocol (PFGE) was performed and revealed four different profiles. Profile 1 (Salmonella Agona), isolated from a pregnant sow, a gilt and two lactating buffaloes, revealed a indistinguishable PFGE pattern, confirming evidences of potential cross-species transmission. Profile 2 (Salmonella Agona), 3 (Salmonella Senftenberg) and 4 (Salmonella Schwarzengrund), isolated from pigs, revealed important indistinguishable PFGE patterns, evidencing Salmonella infection within the pig production phases. Considering the epidemiological relevance of buffaloes and pigs in the cycle of Salmonella infection, confirmation of a potential cross-species transmission of Salmonella Agona and potential Salmonella infection within the pig production phases highlights the importance of the correct establishment of preventive health strategies in farms, in special the importance of avoiding contact between buffaloes and pigs, since cross-species transmission can occur, increasing the risk of spreading the disease.